Challenges in engineering large customized bone constructs. Issue 6 (9th February 2017) - Forrestal, David P.; Klein, Travis J.; Woodruff, Maria A.
ABSTRACT: The ability to treat large tissue defects with customized, patient‐specific scaffolds is one of the most exciting applications in the tissue engineering field. While an increasing number of modestly sized tissue engineering solutions are making the transition to clinical use, successfully scaling up to large scaffolds with customized geometry is proving to be a considerable challenge. Managing often conflicting requirements of cell placement, structural integrity, and a hydrodynamic environment supportive of cell culture throughout the entire thickness of the scaffold has driven the continued development of many techniques used in the production, culturing, and characterization of these scaffolds. This review explores a range of technologies and methods relevant to the design and manufacture of large, anatomically accurate tissue‐engineered scaffolds with a focus on the interaction of manufactured scaffolds with the dynamic tissue culture fluid environment. Biotechnol. Bioeng. 2017;114: 1129–1139. © 2016 Wiley Periodicals, Inc. Abstract : Advances in fabrication technologies, dynamic culture techniques, and computation simulation are enabling the production of complex biomaterial scaffolds integrated with live cells. These scaffolds offer the prospect of creating large engineered bone grafts, tailored specifically to unique patient anatomy. This review presents recent progress and remaining challenges in the production, culture and analysis of large patient‐specific tissue scaffolds.